Answer:
HGD: 117
FDG: 180
Step-by-step explanation:
Answer:
your the problem
Step-by-step explanation:
Answer:
The equation is always false
Step-by-step explanation:
The formula for calculating the area of a circle is expressed as;
A = πr²
- Area of the pond = πr²
- Area of the path = Area of the path + pond - area of pond
- Area of path = π(r+1.5)² - πr²
Since the area of the path is equal to the area of the pond, hence;
π(r+1.5)² - πr² = πr²
Add πr² to both sides
π(r+1.5)² - πr² + πr² = πr² + πr²
π(r+1.5)² = 2πr²
(r+1.5)² = 2r²
Expand the parenthesis
r²+3r + 2.25 = 2r²
r²+3r + 2.25 - 2r² = 0
-r² + 3r + 2.25 = 0
r² - 3r - 2.25 = 0
Multiply through by 2
2r² - 6.0r - 4.5 = 0
<em>This proves the required equation</em>
<em />
Learn more on area of composite figures here: brainly.com/question/15981553